Obtaining of ZnSe nanocrystals from ZnSe bulk crystals by mechanical milling and chemical vapor deposition in silica matrices - Voloshina, L.I.; Seminko, V.V.; Bespalova, I.I.; Maksimchuk, P.O.; Viagin, O.G.; Masalov, A.A. (Functional Materials, 2017)
In the paper ZnSe nanocrystals were obtained from bulk ZnSe crystal using two different methods: mechanical milling and heating of bulk crystal with subsequent deposition of zinc and selenium in the pores of silica matrix. Both samples demonstrate well-known for ZnSe bulk crystals luminescence band at ~ 500 nm, however its temperature stability is sufficiently higher for nanocrystals obtained by either of two routes than for correspondent bulk sample. Beyond ZnSe luminescence, sample obtained by mechanical milling show ZnO luminescence determined by ZnO layer formed at the surface of ZnSe nanocrystal in oxidative atmosphere."